PENGARUH LIKUIDITAS, SOLVABILITAS, DAN AKTIVITAS TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERDAFTAR DI BURSA EFEK INDONESIA - Ade Reza, Muhammad Ade Reza Sanjaya (Magister Manajemen Universitas Islam Malang, 2024)
This research aims to determine the influence of Current Ratio, Debt to Asset Ratio, and Return On Equity both simultaneously and partially on Profit Growth. This type of research uses quantitative research methods with secondary data. The sample used is the Financial Report of Transportation and Logistics Companies listed on the Indonesia Stock Exchange for the 2020-2023 period. The data analysis method uses the classic assumption test which consists of the multicollinearity test, autocorrelation test and heteroscedasticity test, multiple linear regression analysis and anova test which consists of the correlation coefficient test, coefficient of determination test, F test and t test. The results of this research show that partially the Current Ratio variable has a negative and significant effect on profit growth, the Debt to Asset Ratio variable has a negative effect on profit growth, and Return On Equity has a positive and significant effect on profit growth. Simultaneously Current Ratio, Debt to Asset Ratio and Return On Equity have a significant effect on profit growth.